A comprehensive evaluation of the chemical profiles and biological properties of six geophytes from Turkey: Sources of bioactive compounds for novel nutraceuticals. (February 2021) - Fawzi Mahomoodally, Mohamad; Zengin, Gokhan; Ibrahime Sinan, Kouadio; Yıldıztugay, Evren; Lobine, Devina; Ouelbani, Rayene; Bensari, Souheir; Ak, Gunes; Abdullah Yılmaz, Mustafa; Gallo, Monica; Montesano, Domenico
Graphical abstract: Highlights: Chemical composition and pharmacological properties of 6ix geophytes were determined. All extracts displayed notable antioxidant, anti-acetylcholinesterase and tyrosinase activity. Bioactive compounds such as quinic and fumaric acids were detected. The geophytes could be considered as functional ingredients in food industry. Abstract: Geophytes are gaining interest as sources of natural ingredients in nutraceutical and pharmaceutical area. In this sense, six bulbous plant species from Turkey are investigated, namely Hyacinthella campanulata K.Perss. & Wendelbo, Muscari neglectum Guss. ex Ten., Tulipa humilis herb., Iris stenophylla Hausskn. ex Baker, Galanthus elwesii Hook. f. and Crocus danfordiae Maw. with the aim to highlight their chemical compositions and biological properties. Polyphenolic profiles of the different plant parts (flower, bulb and leaf) of the six genotypes were evaluated using colorimetric methods as well LC–MS/MS. The antioxidant properties and enzymes inhibitory potential (α-amylase, α-glucosidase, tyrosinase and cholinesterases) of the extracts were determined. Overall, highest total phenolic content and total flavonoid content were observed in the leaf extracts of the studied species, except for M. neglectum (flower extract) and T. humilis (flower extract). LC–MS/MS analysis revealed the abundance of some phenolic compounds including quinic acid, hesperidin and chlorogenic acid in selective extracts. The extracts showed significant antioxidant potentials, with leaf extract of the I. stenophylla being more potent, which is linked to its high phenolic contents. All the extracts displayed notable anti-acetylcholinesterase (1.77 – 2.53 mg GALAE/g) and tyrosinase (54.9–67.20 mg KAE/g). Selective extracts have showed activity against butyrylcholinesterase, with bulb extract of M. neglectum (2.99 mg GALAE/g), I. stenophylla (2.53 mg GALAE/g) and G. elwesii (2.52 mg GALAE/g) showing highest activity. Modest activity was observed against α-amylase and α-glucosidase. The experimental data gathered herein is the first report on the phytochemical and biological attributes of these bulbous plant species which project them as potential sources of biologically active compounds for phytomedicines and nutraceuticals development.